The Effect Of Service Quality To Customer Satisfaction Of D’Primahotel Bandung - Salsabila, Naura; Millanyani, Heppy (eProceedings of Management, 2023)
D'primahotel Bandung is a 4-star hotel located in Sukajadi area, Bandung. It has a building of 6000 m2 with eightfloors, equipped with guest room facilities, swimming pool, playground, ballroom, and meeting room. Based onreviews from visitors on the website Traveloka.com there are negative review about the problems complained byconsumers. The negative assessment must certainly be handled, so that the company can defend against the emergenceof competitors in similar business fields. This study aims to determine the quality of service in which there aredimensions of tangible, reliability, responsiveness, assurance and empathy to consumers from D'primahotel Bandung.The results of this research are expected to be used as input for companies when formulating strategies in competing.The method used in this research is a quantitative method, namely descriptive and causal research. The technique usedin sampling is Non-Probability Sampling with the type of Purposive Sampling using a questionnaire with 384respondents. This study used multiple linear regression data analysis techniques, using SPSS software. The hypothesisshows that the variables tangible, reliability, responsiveness, assurance, and empathy have a positive and significantrelationship with consumer satisfaction variables both partially and simultaneously.Keywords-service quality, customer satisfaction